Narrative Analysis of Peace-Loving Character Values in Surah al-Hujurat (Verses 9–13) and Their Relevance to Religious Moderation Education - Gibran, M.; Jamin, Ahmad; Yahya, Usman (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
This research is motivated by the decline of moral values in society, as reflected in the increasing number of conflicts among community groups, mass organizations, ethnicities, and cultures, some of which have led to bloodshed and loss of life. Alarmingly, such conflicts also occur among intellectuals. This situation calls for strategic efforts to restore social harmony, one of which is by instilling the values of religious moderation found in the Qur’an—particularly through strengthening the peace-loving character that fosters tolerance in society. The main objective of this study is to uncover the meaning of the peace-loving character in Surah al-Hujurat verses 9–13 and its relevance to religious moderation education. More broadly, it aims to identify the values of peace conveyed in these verses and their connection to the principles of religious moderation promoted by Indonesia’s Ministry of Religious Affairs. This study uses a qualitative-descriptive method with a library research approach and content analysis technique. The results show that Surah al-Hujurat verses 9–13 contain values such as conflict resolution through justice, respect for differences, and upholding fairness. These values are strongly aligned with the principles of religious moderation, such as tawassuth (middle path), tasamuh (tolerance), tawazun (balance), i’tidal (justice), and iqtishad (moderation). Therefore, these Qur’anic teachings serve as a vital foundation for shaping moderate and tolerant character through Islamic education.